Turismo, capital social e produção do espaço: uma leitura a partir do município de Natal/RN no período de 1980 a 2012 - Maranhão, Christiano Henrique da Silva (2012)
Nowadays, there is a tourism phase in the city of Natal/RN called internationalization of tourism , which shows a tourism model with a planning and an administration, based on the needs of the visitors. Such process shows that the production as well as the reproduction of the city spaces with the goal of favor tourism excludes of its composition the effective participation of local subjects. Thus, the research is a result of the perception of tourism as an activity with a meaningful power of transformation of the social and natural space taking into account the low participation of the residents in the decisions of the tourism activities in the city of Natal/RN. Despite that reality, it is possible to note Natal that civil society, starts to mobilize its citizens trying to develop collective actions to low the negative impacts caused by the bad planning as wells not efficient tourism administration, trying to put in action the right of the local population to take part in the decisions of the city activities. Having this panorama as background, this paper aims at investigating in which way the mobilizing action of the social capital in Natal has contributed to change the spatial production which is part of the process of expansion of tourism in Natal/RN? The research presents a temporal picture which starts in the year of 1980, when occurs the first effective state intervention aiming to develop tourism in the capital, taking into account an analysis of 2012. Concerning the spatial picture, the research investigates the beaches of Natal which concentrates criteria and actions such as: visitation, tourism appeal and focus of investments, highlighting the following beaches: Ponta Negra, Areia Preta, Praia dos Artistas, Praia do Meio, Praia do Forte and Redinha. This study is of a descriptive and exploratory nature concerning its goals. With respect to the treatment of its object it is a qualitative research. The data was collected through structural interviews, with open questions. Regarding the methodological choices, it was used the content analysis proposed as well as the collective discursive subject methodology. The results show that there´s not yet in Natal a meaningful social capital related to tourism, capable to change the spatial production related to the activity. It should be stressed that Natal social capital presents difficulties concerning the incentive to trust, spontaneous cooperation and the civic participation, which are the foundation for the development of an effective social capital, which makes it harder for a more expressive articulation in the reality in Natal/RN. It should be stressed, as an answer to the research questions, that tourism in Natal/RN is represented by social and spatial segregation. In other words it emphasizes mainly the action of hegemonic agents (State and market), leaving little room for the participation of society. It can be noticed that the actions related to tourism in Natal keeps the popular participation out of the way. Thus, it can be said that the social capital in Natal/RN does not yet contribute to a more fair spatial production related to the expansion of the tourism as well as the well being of the population of Natal/RN. In conclusion, it should be taken into account that this participation do exists but not in a meaningful way. In other words, it´s not enough yet to cause meaningful changes in the actions which tourism needs nowadays in Natal/RN